Gaps In Education Quality In Maluku - Abdul Muin (Ittishal Educational Research Journal, 2025)
The gap in education quality in Maluku is a serious challenge that affects educational development in the region. Factors such as limited resources, geographical distance, and unequal access to education are the main causes of unequal education quality between regions in Maluku. The low education budget and lack of educational infrastructure are the main obstacles in improving the quality of education in Maluku. Limited human resources, especially unqualified teaching staff, also contribute to low educational standards. The geographical distance between the islands in Maluku makes it difficult for many schools to access education. There are significant gaps in the availability of educational facilities on remote islands, which has an impact on the quality of education for children in these areas as well as inequality in access to education between social and economic groups. Children from underprivileged families tend to face difficulties in accessing quality education, causing inequality in the quality of education in Maluku to become increasingly sharp. Furthermore, the impacts of this gap in educational quality include low literacy rates, a lack of skills needed to contribute to the local economy, and increased social inequality. Therefore, joint efforts need to be made by the government, community and related parties to overcome the gap in education quality in Maluku. Increasing the education budget, improving the qualifications of teaching staff, and increasing access to education in remote areas must be the main focus in efforts to improve the quality of education and create educational equality throughout Maluku.